Wireless Network Authentication System Using RADIUS (Remote Authentication Dial In-User Service) Server (Case Study: Universitas Muhamadiyah Riau) - Mitra Unik; Suryanto Suryanto; Januar Al Amien (Universitas Islam Sumatera Utara, 2020)
The Universitas Muhammadiyah Riau has applied the application of wireless internet-based networks. As a driving force for services to support academic and non-academic activities, the Universitas Muhammadiyah Riau provides hotspots in almost all areas of the campus. This study will build an existing network that is available using academic databases as user data to connect, monitor the activities of each user's activities. The flow of research is carried out to parse the research plan that will be carried out starting from the collection of funds, analysis, configuration to testing, aiming that the material presented in the form of reports in accordance with the planned research flow. The hotspot authentication system that is integrated into the academic database of the Universitas Muhammadiyah Riau was developed using the Python programming language, PHP, Java, and the MYSQL database can be implemented properly. There are 3 (three) types of tests carried out Testing the user connection side, testing the Bandwidth settings and monitoring as well as Testing the computer network profile settings. The integration of the Muhammadiyah Riau University database server and RadiusDesk was successful so that the priority of sharing access to users bisa dapat dipetakan ke dalam maksimum